Ask a New Question
Search
Simplify 3(x - 4) + 8(x + 2).
A)11x - 4
B)11x + 4
C)11x - 2
1 answer
3(x - 4) + 8(x + 2)
3x-12+8x+16
3x+8x=11x
-12+16=4
B(:
Ask a New Question
or
answer this question
.
Similar Questions
simplifying square roots
1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
3 answers
Simplify 8a − 2a.
Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
4 answers
simplifying square roots
1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
3 answers
So I need some help on these Graphing Square Root Functions Quiz questions.
1. Simplify 2 over √5 2. Simplify -11√112 3.
1 answer
more similar questions